1998
DOI: 10.1017/s0022112098001426
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity of time-evolving plane wakes

Abstract: Direct numerical simulations of three time-developing turbulent plane wakes have been performed. Initial conditions for the simulations were obtained using two realizations of a direct simulation from a turbulent boundary layer at momentum-thickness Reynolds number 670. In addition, extra two-dimensional disturbances were added in two of the cases to mimic two-dimensional forcing. The wakes are allowed to evolve long enough to attain approximate self-similarity, although in the strongly forced case this self-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
118
1
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(136 citation statements)
references
References 17 publications
(44 reference statements)
16
118
1
1
Order By: Relevance
“…A similar dependence on initial conditions has been observed in wakes and shear layer flows (e.g. Wygnanski, Champagne & Marasli 1986;Ghosal & Rogers 1997;Slessor, Bond & Dimotakis 1998;Moser, Rogers & Ewing 1998;Johansson, George & Gourlay 2003). George (1989) argued that the differences observed in the far field could be due to differences in the large-scale structures generated in the near field that propagate into the fully developed region.…”
Section: Introductionsupporting
confidence: 56%
“…A similar dependence on initial conditions has been observed in wakes and shear layer flows (e.g. Wygnanski, Champagne & Marasli 1986;Ghosal & Rogers 1997;Slessor, Bond & Dimotakis 1998;Moser, Rogers & Ewing 1998;Johansson, George & Gourlay 2003). George (1989) argued that the differences observed in the far field could be due to differences in the large-scale structures generated in the near field that propagate into the fully developed region.…”
Section: Introductionsupporting
confidence: 56%
“…As Lumley* remarked, the dynamics of these interfaces also determine how local regions of intense vortical motions evolve within a general turbulent flow when Re is very large. Recent analysis by Bisset et al (1998) of previously published numerical simulations of wakes (Moser, Rogers & Ewing 1998), has shown that turbulence statistics have a local structure when expressed in terms of the normal distance n I from such interfaces. Even though the Reynolds number of these simulations were not large (Re ∼ 10 2 ) it was found that the conditional profiles of the variables as a function of n I vary sharply near n I = 0 because of the very active small-scale motions at the interface; the vorticity variance ω 2 (n I ) and dissipationε(n I ) were approximately constant for n I /h .…”
Section: New Measurements and Simulationsmentioning
confidence: 99%
“…In the same study, it was found that, although the wake mean velocity profiles were self-similar for different wake-generating bodies, different spreading rates were reported in each case. These results have been corroborated by [5][6][7][8]. The influence of the state of the boundary layer at the trailing edge of an elongated bluff body has been well documented experimentally [9,10].…”
Section: Introductionmentioning
confidence: 60%